Effect of Enteral Nutrition in Child Surgical Cases - Catur Suzantara Sutisna (Science Midwifery, 2022)
This study aims to determine the effect of enteral nutrition in pediatric surgical cases while data collection was carried out on several relevant literature studies using databases, Pubmed journals and Google Scholar, the results showed that enteral nutrition in the postoperative period should be carried out regularly. adequate through the process of excessive body muscle proteolysis and at an advanced stage. Energy expenditure will also increase in surgical trauma as a result of hormonal responses, this situation is in anticipation of early nutrition by means of enteral nutrition which will lead to faster recovery and wound healing and prevent complications so that the patient's length of stay will be shorter and indirectly will also reduce the costs incurred for the treatment of patients. Enteral nutrition in children is acceptable, tolerated, and provides a good response to nutritional status with such good acceptance of enteral nutrition that nutritional support aimed at achieving or at least maintaining optimal nutritional status can be implemented because there is less food left, so that Enteral nutrition can be used as an alternative to good nutritional support for children, this process also becomes a reference for the increased serum albumin and prealbumin values in most subjects and no weight loss occurs.